The age of alkohol initiation among patients treated for addiction - Opielak, Grzegorz; Cyganok, Mikołaj; Zawiślak, Jacek; Putowski, Maciej; Podgórniak, Marta; Maciejewski, Ryszard (Current Problems of Psychiatry, 2015)
Introduction: According to WHO, alcohol is considered to be one of the three main risk factors for the health of the population. Each year about 3,3 million of people on the World die due to excessive alcohol consumption, and alcohol dependence is classified as a disease. Alcohol abuse has a negative impact on all systems of the body, however, the greatest influence is noted in relation to the central nervous system, where the irreversible neurodegenerative changes take place. The aim of the study: The aim of the study is to analyze the age of alcohol initiation among patients treated for addiction taking into account variables such as age, sex, place of residence and level of education. Material and methods: The material for the analysis are data collected from 121 patients from Lublin province of various ages with different levels of education, first-time or again hospitalized at the detoxification ward in the Neuropsychiatric Hospital in Lublin. Results: The average age of an alcohol initiation in the examined group of patients treated for addiction was 16,5 years of age. The earliest recorded age of an alcohol initiation in this group was 11, while the latest one 25 years of age. As many as 75% of patients experienced their first contact with alcohol before the age of 18 years. The analysis of data revealed a statistically significant difference between the age of the alcohol initiation and the level of education obtained in later life.